Production - Foreign - Oil and Gas in Iran - Courtesy of Anglo-Iranian Oil Co. (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1937)
Masjid-i-Sulaiman Field.—During the past year, drilling activities have been limited to repair work. No new developments of importance can be recorded in production technique. Fall of dome pressure is maintained at the 1 lb. per sq. in. per annum rate mentioned in previous reports. Acid treatment of wells is being increasingly used and for wells in fissured areas has been very successful. Such wells have been converted into first-grade producers with substantial drops in bottom-hole differential pressures. The effect of acid treatment has been to increase the flowing lives of wells so treated. The normal procedure consists of threo treatments of 500 gal. commercial acid diluted 100 per cent but success has been met with fewer applications. The policy of returning products to the resorvoir has been continued. The total quantity of products returned since the policy was commenced in 1929 now amounts to approximately 30 million barrels. Haft Kel Field.—The drilling of the main Haft Kel structure for production purposes has now been completed. Production and control wells have been completed to meet the rate of production anticipated over the next few years.